Pathologically oriented descriptive study of male genital circumcisions across medical and surgical specialties. (15th December 2020) - Mazzoni, Daniel; Pool, Louis; Muir, Jim
Abstract: Background: Circumcision is one of the most frequently performed procedure by clinicians, yet its role and indication in clinical practice lacks consensus and remains unclear. We sought to evaluate a collection of male circumcisions to determine the range of indications, histopathological diagnoses, and type of clinicians associated with circumcision. Methods: We performed a retrospective descriptive cohort study of male patients who received a circumcision reported by one major dermatopathology laboratory between January 2017 and December 2018. Data were extracted from the histological report of the pathologist for each case. Patient age, type of clinician, clinical notes, and histopathological diagnosis were evaluated. Results: "/> A total of 406 circumcisions were identified. The median age for circumcision was 36 (IQR 16‐61). Boys less than 18 years of age made up 24% (98/406). Histological diagnoses included normal (43/406, 11%), nonspecific inflammation (82/406, 20%), inflammatory conditions (264/406, 65%), infections (9/406, 2.2%), benign neoplasms (5/406, 1.0%), and scar tissue (3/406, 0.7%). The most common diagnosis was balanitis xerotica obliterans (226/406, 56%). Rarely, genital infections and neoplastic lesions were identified. Circumcisions were performed by urologists (289/406, 71.2%), general practitioners (76/406, 18.7%), general surgeons (32/406, 8%), pediatric surgeons (5/406, 1%), and dermatologists (4/406, 1%). The main indications for circumcision were phimosis (110/202, 54%), suspected lichen sclerosus (28/202, 14%), and balanitis (15/202, 7%). Conclusion: Circumcision was performed for a broad range of genital dermatoses across various medical and surgical specialties. Few studies have described these observations. We discuss the common pathological conditions leading to circumcision and its role in diagnosis and treatment.